(untitled) - Axelrod, Herbert R. (U.S.A., 1989)
the book is on fish diseases. It introduces what ogranisms have infected fish and helped to find treatments for them. The various charts help narrow down all the possiblities of disease that a fish may have. Besides, this book to any fish hobbist that is interested in finding cures for the diseases that have effected their fish, beginners and advanced.
Keywords: Fishes; Diseases